Clinical prioritisations of healthcare for the aged—professional roles. Issue 5 (30th April 2008) - Nortvedt, P; Pedersen, R; Grøthe, K H; Nordhaug, M; Kirkevold, M; Slettebø, Å; Brinchmann, B S; Andersen, B
Abstract : Background: Although fair distribution of healthcare services for older patients is an important challenge, qualitative research exploring clinicians' considerations in clinical prioritisation within this field is scarce. Objectives: To explore how clinicians understand their professional role in clinical prioritisations in healthcare services for old patients. Design: A semi-structured interview-guide was employed to interview 45 clinicians working with older patients. The interviews were analysed qualitatively using hermeneutical content analysis. Participants: 20 physicians and 25 nurses working in public hospitals and nursing homes in different parts of Norway. Results and interpretations: The clinicians struggle with not being able to attend to the comprehensive needs of older patients, and being unfaithful to professional ideals and expectations. There is a tendency towards lowering the standards and narrowing the role of the clinician. This is done in order to secure the vital needs of the patient, but is at the expense of good practice and holistic role modelling. Increased specialisation, advances and increase in medical interventions, economical incentives, organisational structures, and biomedical paradigms, may all contribute to a narrowing of the clinicians' role. Conclusion: Distributing healthcare services in a fair way is generally not described as integral to the clinicians' role in clinical prioritisations. If considerations of justice are not included in clinicians' role, it is likely that others will shape major parts of their roles and responsibilities in clinical prioritisations. Fair distribution of healthcare services for older patients is possible only if clinicians accept responsibility in these questions.